2021
DOI: 10.36740/wlek202102118
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Blood Marker of Hypertrophy– Cardiotrophin-1 When Carrying Different Variants of Its Gene in Men With Essential Hypertension

Abstract: The aim: To improve diagnosis of essential hypertension with left ventricular hypertrophy and chronic heart failure in men citizens of Podillya region in Ukraine by determining the plasma levels of cardiotrophin-1 in patients with different CT-1 gene variants. Materials and methods: A total of 70 men with no signs of cardiovascular disease and 100 patients with essential hypertension were examined. Among those, 50 participants had hypertension and left ventricular hypertrophy. Other 50 patients had hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…A clinical study by M. O. Matokhniuk et al has revealed a correlation between plasma CT and LV myocardial mass index in the patients with heart failure [19]. The same result presented study by U. Polat et al can be used as a new biomarker and correlated with standard markers of myocardial ischemia [20].…”
Section: Original Researchmentioning
confidence: 57%
“…A clinical study by M. O. Matokhniuk et al has revealed a correlation between plasma CT and LV myocardial mass index in the patients with heart failure [19]. The same result presented study by U. Polat et al can be used as a new biomarker and correlated with standard markers of myocardial ischemia [20].…”
Section: Original Researchmentioning
confidence: 57%
“…In patients with LVH and heart failure mediated by hypertension, the levels of CT-1 are increased, and plasma CT-1 level ≥122,895 pg/mL can be used for early diagnosis of changes in myocardial structure such as left ventricular hypertrophy, and plasma CT-1 levels ≥303.81 pg/mL for early detection of combined heart failure [33]. However, this study only included male patients and the sample was small.…”
Section: Cardiotrophinmentioning
confidence: 99%
“…Так, серед мешканців Подільського регіону України діагностичне та прогностичне значення мозкового (МНП) та судинного натрійуретичного пептидів (СНП) при поліморфізмі успадкування гена рецептора ангіотензину ІІ 1-го типу (АТ1Р) вивчали О. Л. Старжинська [17] у чоловіків; О. О. Сакович [16], С. В. Франчук [7] у жінок; у носіїв різних варіантів гена мозкового натрійуретичного пептиду -Ю. П. Пашкова [13] у чоловіків; Л. М. Сурсаєва [18] у жінок. Вплив поліморфізму гена альдостеронсинтетази (CYP11B2) на плазмовий рівень МНП досліджувала М. С. Лозинська [11], діагностичне та клінічне значення кардіотрофіну-1 у чоловіків при поліморфізмі кодуючого гена -М. О. Ма-тохнюк [12]. В. О. Ружанська [15] оцінила прогностичні та діагностичні можливості галектину-3 та МНП при поліморфізмі гена АТ1Р у чоловіків Подільського регіону.…”
Section: вступunclassified